Enterobacter cloacae infection of an expanded polytetrafluoroethylene femoral-popliteal bypass graft: a case report - Musil, Ian (BioMed Central, 2010)
INTRODUCTION: Enterobacter cloacae infections are common among burn victims, immunocompromised patients, and patients with malignancy. Most commonly these infections are manifested as nosocomial urinary tract or pulmonary infections. Nosocomial outbreaks have also been associated with colonization of certain surgical equipment and operative cleaning solutions. Infections of an aortobifemoral prosthesis, an aortic graft, and arteriovenous fistulae are noted in the literature. To our knowledge, this is the first isolated account of an E. cloacae infection of a femoral-popliteal expanded polytetrafluoroethylene bypass graft. CASE PRESENTATION: A 68-year-old Caucasian man presented with fever and rest pain in the right lower extremity five months after the placement of a vascular expanded polytetrafluoroethylene graft for femoral-popliteal bypass. Computed tomography angiography demonstrated peri-graft fluid that was aspirated percutaneously with image guidance and cultured to reveal E. cloacae. The graft was revised and then removed. The patient completed a six-week course of ceftazidime and is currently without signs of infection. There were no other reports of E. cloacae graft infections in any patients receiving treatment in the same surgical suite within a month of this report. CONCLUSION: Isolated cases of E. cloacae infection of surgical bypass grafts are rare (unique in this setting). Clinicians should have a high index of suspicion for device contamination in such cases and should consider testing for possible microbial reservoirs. Graft removal is required due to the formation of biofilm and the recent emergence of Enterobacteriaceae producing extended-spectrum beta-lactamase in community acquired infections.